"This Could Be Me": Simulation of Refugee Experiences. (2nd January 2022) - Maton, Rhiannon M.; Carrick-Hagenbarth, Jessica
Abstract: The authors discuss how the kinesthetic, affective, and conceptual learning triggered through simulation can support future teachers in building empathy for refugees and immigrants.